PENGARUH LUAS LAHAN DAN TENAGA KERJA PERTANIAN TERHADAP PRODUK DOMESTIK BRUTO SEKTOR PERTANIAN DI INDONESIA - Nadila Sari; Hijri Juliansyah (LPPM Universitas Malikussaleh - Indonesia, 2024)
This research aims to determine the influence of agricultural land area and agricultural labor on GDP of the agricultural sector in Indonesia. This research uses secondary data for the period 1987-2021 obtained from the Food and Agriculture Organization (FAO). The study employs VectorAutoregressive (VAR). The results showed that agricultural land area has a positive and significant effect on GDP in the agricultural sector, while agricultural labor has a negative and significant effect on the GDP of agricultural sector